Prediction of Corona anxiety based on personality characteristics and self-discipline in vaccinated people at the vaccination center of the Prophet's (PBUH) complex - Borminejad, Leila; Banisi, Parinaz; Barkhordari, Fatemeh; Haghani, Shima; Farhadi Afshar, Parnian; Jalilzadeh, Mahdieh; Delfanazari, Ghanbarali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The rapid spread and epidemic, its high mortality rate and the absence of any definite and approved treatment and medicine for Corona have caused severe disorders. The aim of the current research was to predict corona anxiety based on the personality characteristics of self-care in vaccinated people at the vaccination center. Method: The method of the current research is quantitative and has been implemented in a descriptive-correlational way, and it is practical in terms of the purpose of this research. The study population of this research is all the people who visited the vaccination center of the Holy Prophet (PBUH) Complex of West Tehran Azad University in the Fall 2021. Among these people, 400 vaccinated people who received the second dose were selected as a sample based on the amount calculated by Gpower software in a simple random manner. Personality, self-diagnosis and corona anxiety tests were taken from the subject. The data were analyzed using the statistical method SEM. Results: The results show that Corona anxiety is predicted based on personality traits and self-diagnosis. The path coefficient of neuroticism (P